1993
DOI: 10.1055/s-2007-1002103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Progesterone Action by a Factor in Human Follicular Fluid

Abstract: A factor was found in human follicular fluid that blocked progesterone-stimulated net uptake of 45Ca2+ in human sperm and progesterone-induced maturation of Xenopus oocyte. The factor was partially purified by ultrafiltration through PM-10 membrane and gel filtration on Sephadex G-25 column. The active fraction is effective at a concentration of 200 micrograms/ml. The present findings suggest that hFF factor may regulate the metabolism of progesterone sensitive cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Follicular fluid is also widely used as physiological AR stimulus (Suarez et al, 1986) and as once-reacted sperm do not further bind to the oocyte (Liu & Baker, 1990) it can be expected that in the presence of hFF there should be an increase in the proportion of reacted cells. Juneja et al (1993) purified a fraction of hFF which inhibited progesteronestimulated sperm calcium uptake, suggesting that other compounds or molecules in hFF could interfere with the stimulating effect of progesterone. As spermatozoa must be incubated for at least 6 h to undergo hFF-induced AR (Calvo et al, 1989), this loss in the ability to interact with the ZP should not be associated with an increase in the proportion of acrosome-reacted cells (previous experiments in our laboratory tested the ability of the hFF pool to induce the AR on 22-h capacitated spermatozoa, resulting in a 100% increase in reacted cells versus controls, data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Follicular fluid is also widely used as physiological AR stimulus (Suarez et al, 1986) and as once-reacted sperm do not further bind to the oocyte (Liu & Baker, 1990) it can be expected that in the presence of hFF there should be an increase in the proportion of reacted cells. Juneja et al (1993) purified a fraction of hFF which inhibited progesteronestimulated sperm calcium uptake, suggesting that other compounds or molecules in hFF could interfere with the stimulating effect of progesterone. As spermatozoa must be incubated for at least 6 h to undergo hFF-induced AR (Calvo et al, 1989), this loss in the ability to interact with the ZP should not be associated with an increase in the proportion of acrosome-reacted cells (previous experiments in our laboratory tested the ability of the hFF pool to induce the AR on 22-h capacitated spermatozoa, resulting in a 100% increase in reacted cells versus controls, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…While Sueldo et al (1993) reported that addition of 1 lg ml )1 progesterone is enough to enhance sperm binding in the HZA, in the present study an 8-fold higher progesterone concentration in final incubation medium did not increase the ZP binding. Juneja et al (1993) purified a fraction of hFF which inhibited progesteronestimulated sperm calcium uptake, suggesting that other compounds or molecules in hFF could interfere with the stimulating effect of progesterone. Carbohydrate-binding proteins on the sperm surface mediate gamete recognition by binding with both high affinity and high specificity to complex glycoconjugates on the ZP (Miranda et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A non-steroid factor (resistant to boiling and trypsin) has been found in human follicular fluid that blocked progesterone-stimulated 45Ca2 + uptake in human sperm, and it was proposed that the factor may regulate capacitation and modulate the metabolism of progesterone-sensitive cells (Juneja et al, 1993). Meizel & Turner (1993) showed that polyamine biosynthesis was necessary for the progesterone-initiated rapid increase in [Ca2 'Ii and acrosome reaction, because two polyamine biosynthesis suicide inhibitors partially blocked the effect of progesterone on [Ca2+Ii.…”
Section: Other Effects Of Progesterone On Human Spermmentioning
confidence: 99%